Early Life Risk Factors in Pediatric EoE: Could We Prevent This Modern Disease? - Votto, Martina; Marseglia, Gian Luigi; De Filippo, Maria; Brambilla, Ilaria; Caimmi, Silvia Maria Elena; Licari, Amelia (Frontiers in Pediatrics, 2020)
Eosinophilic esophagitis (EoE) is a chronic antigen-mediated inflammatory disease that affects the esophagus. In the last 20 years, a large number of epidemiological studies showed a significant increase in the incidence and prevalence of EoE, especially in developed countries. This phenomenon might correlate to the overall increase in pediatric allergic diseases or might be a result of improved medical awareness and knowledge through modern diagnostic instruments. Since 1993 when EoE was first recognized as a distinct clinical entity, several signs of progress in the pathophysiology of EoE were achieved. However, few studies reported data on early risk factors for pediatric EoE and how these factors may interfere with genes. Currently, the most defined risk factors for EoE are male sex, Caucasian race, and atopic comorbidities. Other putative risk factors may include alterations in epithelial barrier function and fibrous remodeling, esophageal dysbiosis, variation in the nature and timing of oral antigen exposure, and early prescription of proton pump inhibitors and antibiotics. Notably, the timing and nature of food antigen exposure may be fundamental in inducing or reversing immune tolerance, but no studies are reported. This review summarized the current evidence on the risk factors that might contribute to the increasing development of EoE, focusing on the possible preventive role of early interventions.